Il sistema formativo integrato in Franco Frabboni - Trebisacce, Giuseppe (Studi sulla Formazione/Open Journal of Education, 2011)
The author deals with a subject very dear to Franco Frabboni, the integrated training system, starting from the notion of territory and the analysis of the school crisis. The changes in society lead us to think of an expanded education and training system where the many educational agencies must work together for the realization operative strategies, which aretailored to the needs of the many new social subjects. It is especially in the South of Italy that this system could be fruitful and Frabboni has always looked and reflected carefully in its numerous works on these historical and social issues.